ANALISIS STRATEGI PROMOSI UNTUK MENINGKATKAN KUNJUNGAN WISATAWAN PADA DINAS PARIWISATA PROVINSI BENGKULU - Rahmadani Rahmadani (UM. Bengkulu, 2026)
Tourism is a strategic sector that plays an important role in driving regional economic growth and improving community welfare. Bengkulu Province has diverse tourism potential, including natural, cultural, and historical attractions; however, tourist visit levels have not yet reached optimal conditions. This situation requires effective and well-planned promotional strategies implemented by the Bengkulu Province Tourism Office. This study aims to analyze tourism promotion strategies in increasing tourist visits through the marketing mix (4P) approach, consisting of product, price, place, and promotion. This research employs a descriptive qualitative approach and was conducted at the Bengkulu Province Tourism Office. Data were collected through in-depth interviews with officials and staff of the Tourism Office, field observations, and documentation. Research informants were selected using snowball sampling techniques. Data analysis was carried out using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The results indicate that the implementation of the tourism marketing mix in Bengkulu Province has generally been carried out fairly well. In the product aspect, Bengkulu offers diverse tourism attractions; however, product packaging and supporting facilities at several destinations still require improvement. The price aspect shows that pricing is relatively affordable and in accordance with regulations, although it is not yet fully proportional to service quality at some locations. The place aspect indicates that accessibility remains a major constraint, particularly for nature-based tourism destinations located in regency areas. Meanwhile, the promotion aspect emerges as the most effective component through the use of digital media, the organization of cultural events, and collaboration with tourism stakeholders. The study concludes that tourism promotion strategies in Bengkulu Province have positively contributed to increasing exposure and tourist interest, yet further strengthening is needed in product development, accessibility improvement, price consistency, and the integration of promotion with destination readiness. Keywords: promotion strategy, marketing mix, tourism, tourist visits, Bengkulu.